2021
DOI: 10.1590/0102-33062020abb0370
|View full text |Cite
|
Sign up to set email alerts
|

How hidden is the diversity of the genus Cosmarium (Desmidiaceae) in the Brazilian Caatinga?

Abstract: The Caatinga domain is the largest and most diverse tropical semiarid ecoregion of South America; however, little is known about the diversity of desmids it harbors, especially the genus Cosmarium (Desmidiaceae, Zygnematophyceae). Our study contributes to the knowledge of Cosmarium in the Caatinga through the report of 42 interesting taxa, including a new species (Cosmarium imperiale), 22 new records for South America, and 19 additions to the desmid flora from Brazil. The samples were gathered from periphytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Over 600 Cosmarium taxa were recorded for Brazil (Biolo & Bicudo 2018), and the genus was more intensively studied in the south region where numerous taxonomic studies revealed its presence in both phytoplankton and periphyton of reservoirs and rivers. Recent floristic studies recording the presence of Cosmarium in Brazil include States such as Paraná (Silva & Cecy 2004, Bortolini et al 2010, Felisberto & Rodrigues 2010, Biolo et al 2013, Menezes et al 2011, Carvalho et al 2015, Aquino et al 2016, Osório et al 2018, Rodrigues & Moresco 2021), São Paulo (Bicudo et al 2019, Felisberto & Rodrigues 2010, Bahia (Oliveira et al 2010, Oliveira et al 2011, Oliveira et al 2016, Ramos et al 2018, Ramos et al 2021, Goiás (Felisberto & Rodrigues 2004), Distrito Federal (Estrela et al 2011), Amazonas (Saturnino et al 2020), Sergipe (Burle et al 2020), Mato Grosso and Rio de Janeiro (Kanetsuna 2004). Furthermore, in the last 10 years five new species of Cosmarium were described based on Brazilian material: Cosmarium bahianum G.J.P.…”
Section: Introductionmentioning
confidence: 99%
“…Over 600 Cosmarium taxa were recorded for Brazil (Biolo & Bicudo 2018), and the genus was more intensively studied in the south region where numerous taxonomic studies revealed its presence in both phytoplankton and periphyton of reservoirs and rivers. Recent floristic studies recording the presence of Cosmarium in Brazil include States such as Paraná (Silva & Cecy 2004, Bortolini et al 2010, Felisberto & Rodrigues 2010, Biolo et al 2013, Menezes et al 2011, Carvalho et al 2015, Aquino et al 2016, Osório et al 2018, Rodrigues & Moresco 2021), São Paulo (Bicudo et al 2019, Felisberto & Rodrigues 2010, Bahia (Oliveira et al 2010, Oliveira et al 2011, Oliveira et al 2016, Ramos et al 2018, Ramos et al 2021, Goiás (Felisberto & Rodrigues 2004), Distrito Federal (Estrela et al 2011), Amazonas (Saturnino et al 2020), Sergipe (Burle et al 2020), Mato Grosso and Rio de Janeiro (Kanetsuna 2004). Furthermore, in the last 10 years five new species of Cosmarium were described based on Brazilian material: Cosmarium bahianum G.J.P.…”
Section: Introductionmentioning
confidence: 99%
“…Over 600 Cosmarium taxa were recorded for Brazil (Biolo & Bicudo 2018), and the genus was more intensively studied in the south region where numerous taxonomic studies revealed its presence in both phytoplankton and periphyton of reservoirs and rivers. Recent floristic studies recording the presence of Cosmarium in Brazil include States such as Paraná (Silva & Cecy 2004, Bortolini et al 2010, Felisberto & Rodrigues 2010, Biolo et al 2013, Menezes et al 2011, Carvalho et al 2015, Aquino et al 2016, Osório et al 2018, Rodrigues & Moresco 2021), São Paulo (Bicudo et al 2019, Felisberto & Rodrigues 2010, Bahia (Oliveira et al 2010, Oliveira et al 2011, Oliveira et al 2016, Ramos et al 2018, Ramos et al 2021, Goiás (Felisberto & Rodrigues 2004), Distrito Federal (Estrela et al 2011), Amazonas (Saturnino et al 2020), Sergipe (Burle et al 2020), Mato Grosso and Rio de Janeiro (Kanetsuna 2004). Furthermore, in the last 10 years five new species of Cosmarium were described based on Brazilian material: Cosmarium bahianum G.J.P.…”
Section: Introductionmentioning
confidence: 99%